2021
DOI: 10.1128/msphere.00214-21
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of TonB-Like Proteins in the Heterocyst-Forming Cyanobacterium Anabaena sp. PCC 7120

Abstract: The genomes of many organisms encode more than one TonB protein, and their number does not necessarily correlate with that of TonB-dependent outer membrane transporters. Consequently, specific as well as redundant functions of the different TonB proteins have been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…PCC7120 (previously Anabaena sp. PCC7120) (Schätzle et al, 2021), we focus on the deeply branching strain of Pseudanabaena sp. PCC7367.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PCC7120 (previously Anabaena sp. PCC7120) (Schätzle et al, 2021), we focus on the deeply branching strain of Pseudanabaena sp. PCC7367.…”
Section: Introductionmentioning
confidence: 99%
“…The permease, cFTR1, takes up Fe(III) possibly by re‐oxidation of Fe(II) by oxygen (Xu et al, 2016). Potentially the TonB – ExbB/D complex coordinates with TBDTs to take up iron that is bound to organic ligands (Boukhalfa & Crumbliss, 2002; Jiang et al, 2015; Schätzle et al, 2021). ExbB/D was also found to take up inorganic iron directly (Jiang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of TonB proteins in distinct functions other than iron acquisition has been reported, such as the involvement of P. aeruginosa TonB3 in twitching motility and type IV pili assembly ( Huang et al., 2004 ), S. maltophilia TonB1 in β-lactam susceptibility ( Calvopiña et al., 2020 ), and Anabaena sp. TonB2 in outer membrane integrity ( Schätzle et al., 2021 ). The hemP-hemA-Smlt0796-Smlt0797 operon is repressed by Fur in iron-replete conditions ( Figure 6A ).…”
Section: Discussionmentioning
confidence: 99%
“…They perform the roles with TonB genes to transport the energy of the proton-motive force to outer membrane receptors in Serratia marcescens for the assimilation of iron. Schätzle et al (2021) also reported how these genes were produced by Pseudomonas putida WCS358 and involved in ferric-pseudobactin transport and siderophore production. fecR and pvdD genes that encode iron (III) dicitrate transmembrane sensor protein and pyoverdine sidechain non-ribosomal peptide synthetase were abundant in the HR.…”
Section: Discussionmentioning
confidence: 99%